(untitled) (Práxis Educativa, 2013)
This study aims to analyze the perception of young students in rural and urban schools on politics, human rights and citizenship, as well as to propose reflections on challenges and possible contributions of history teaching to the citizen education of these individuals. 130 young students from the cities of Araguari, Uberlândia and Patos de Minas in the State of Minas Gerais took part in the study. The research subjects can be considered “poor youngsters” according to their family income. It was concluded that rural and urban environments in these towns are social, economical and cultural independent spaces. In relation to politics, the research corroborated international data which reveal the youngsters’ lack of interest, and the rural students were shown more skeptical than the urban ones. Regarding human rights and citizenship, silence was prevalent, mainly amongst the urban young students. The study confirmed the school importance in the formation of a democratic and participant culture, and that one of the challenges to history teachers is to contribute to the field of reflection and education of young students about politics, human rights and citizenship issues. Keywords: Rural and urban youth. Citizenship. History teaching.